Analisis Pengelolaan Informasi Publik Dan Pengaduan Masyarakat Sekretariat Daerah Provinsi Sumatera Selatan - Surniati, Ani; Semil, Nurmah; Iriani, Atrika (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The number of complaints made at the Regional Secretariat of the South Sumatra Province shows that the public does not understand the government agencies that receive and follow up on these complaints. The complaint process is carried out by the Regional Secretariat of the South Sumatra Province. The Regional Secretariat of the South Sumatra Province in its main duties and functions has the obligation to manage public complaints in the field of communication and informatics. The purpose of this study was to analyze the management of public information and public complaints at the Regional Secretariat of South Sumatra Province. The problems in the research are the Bureaucratic System which is too complicated, the lack of socialization in the community regarding complaints and the lack of human resources in the complaint section. The data analysis technique used in this research is qualitative data analysis technique. Overall the management of complaints is good, but there are still some obstacles.